Multi-agent based simulation of team effectiveness in team's task process: a member-task interaction perspective. (6th October 2008) - Dong, Shengping; Hu, Bin
To address the dynamics of team effectiveness with the effect of interactions between task process and members, a multi-agent based model is developed with such concepts as member relation degree and member-task matching degree proposed to describe social relations among team members and how well team members' competences match with task demands respectively. The model is implemented by Repast.J and scenarios are simulated to validate the model in a virtual situation and an actual Chinese team respectively. Validated model are used for analysis of team effectiveness of an actual team and the results are discussed with some suggestions concluded.